Sociodemographic Association of Caregivers Burden with Schizophrenia Disorder (Bangladesh Journal of Medical Science, 2024)
Objective: The aim of this study is to find out a relationship between life satisfaction and caregiver burden among patients who are suffering from psychiatric illness.Materials and methods: The sample size of this study was 170 psychiatric patients. Primarily consent was received from the higher authorities of the psychiatric hospitals and rehabilitation centers in Karachi. Zarit Burden Interview Scale (ZBIS) and Satisfaction with Life Scale (SWLS) were used. Psychiatric patients were divided into schizophrenia disorder (n = 85) and bipolar disorder (n = 85). Data were analyzed by statistics software (SPSS, version, 20.0). The sample was constituted with male 75 (44.1%) and females were 95 (55.9%). The average age range of caregivers was between 19 and 60 years with M = 44.74 and SD = 12.05 years.Results : The results indicated that caregiver burden was a significant predictor of satisfaction with life in patients with schizophrenia disorder [R2, .554; F (1.84) = 36.711, p